The Mantra of Dayak Gawai Tradition as Old Literature Learning for High School Student - Sigit Widiyarto; Dadang Sunendar; Sumiyadi Sumiyadi; Tedi Permadi (Universitas Cokroaminoto Palopo, 2022)
Literature education in schools was still not optimal. Teachers and students still paid less attention to the importance of literature for life. The purpose of this study was to determine the process of learning literature at school in class X high school students, especially mantras. Second, knowing the value contained in the spell. The method used is a qualitative method. There were 5 respondents who live in the village of Ranyai, West Kalimantan. The research process included collecting data by means of interviews, documentation and document review. Techniques of data analysis by collecting data, data reduction, data presentation and conclusions. The results of the study indicated that a process that was well prepared and carried out according to plan, will result in enjoyable literature learning. The process of learning literature could be started from tracing, practical attitudes, introduction and discussion. The values ​​contained in the Gawai Dayak mantra were religious values, educational values ​​and the value of natural balance. This research had implications for the need for literary materials taken from local wisdom, so that Indonesian culture could develop and not became extinct.